Necesidad de reconocimiento y síndrome de selfie: un análisis relacional basado en minería de datos (2017)
The excessive use of social networks in the world is waking the need for recognition in men and women. Be connected the greater part of the day to social networks motivates the obsession with the self-portraits or more known as "Selfies", giving rise to the modern "Selfie Syndrome". This paper presents a data mining model for the feelings analysis that allowed to classify the emotional impact (positive/negative) of the comments published in 250 "Selfies" of men and 250 "Selfies" of women in the social network Facebook. This paper concludes that there is a strong correlation between need for recognition and " Selfie Syndrome". According to the model developed is greater in the female gender, rxy = 0.75, that the male gender, rxy= 0.61, which allows to affirm that the degree of relationship or association between the two variables is good for the female gender unlike male, which indicates that the women are constantly under aesthetics social pressure much greater than men.